Overall Farmstead Assessment - Hickman, John S.; Herbel, Kevin L.; Rogers, Danny H.; Powell, Morgan G. (My University, 1998)
A summary of how to assess farmstead structures and activities.
EP41_1998-08
Keywords: EP41; Equipment and Structures; EP